The Pricing of Emerging Market Country Funds - EUN, C. S. (Institutional Knowledge at Singapore Management University, 2002)
This paper provides an analysis of the equilibrium pricing of closed-end country funds (CECFs) from emerging and nascent markets under the condition of segmented capital markets, where an investment company acquires a set of eligible securities from the home country to form a CECF and issues shares to the residents of the host country. The key findings are: First, a country fund will trade at its net asset value (zero premium), mimicking an open-end status, if the fund acquires as much of eligible securities as the differential ‘substitution’ demand for them between the host and home country investors. The differential substitution demand is shown to represent the equilibrium demand for eligible securities by the host country investors when they do not face supply restrictions. Second, the fund will command a higher premium, the more close a substitute the fund is for the market portfolio of the home country, and the more risk-averse the home country investors are collectively. Third, the basic functional form of the fund premium is robust to the inclusion of freely tradable securities. However, the fund premium would additionally depend on the spanning ability of freely tradable securities.